Dynamic reactivity of biomolecules; a synergy between theory and experiment - Vu, Huyen Trang (Nanyang Technological University, 2020)
Elevated levels of oxidative stress caused by reactive oxygen species (ROSs) are linked to a variety of degenerative diseases including cancer, cardiovascular disease, dementia and ageing in general. Reactive species damages vital biological components in the body causing these ageing diseases. Antioxidants alleviate oxidative stress. Theaflavin is a natural polyphenolic antioxidant found in black tea; the most consumed manufactured drink in the world is tea. Its antioxidant properties established at the physiological scale, yet atomistic understanding is lacking, and thus, the potential for optimisation too. Thereby, a comprehensive conformational study of the antioxidant tea theaflavin by high-level computation density functional theory (DFT) was initiated. Exploration of the structural properties of neutral theaflavin using the theoretical methodology Becke-3-Lee Yang Parr (B3LYP) method together with the basis set 6-31G(d,p), in the gas and aqueous phase, for a full systematic conformational analysis. The conformational search yielded 153 distinct local energy minima conformers which suggest that theaflavin is a flexible antioxidant. The benzotropolone moiety (a characteristic of black tea) is the backbone to the energetic stability of theaflavin, alongside the extensive network of intramolecular interactions formed. The theoretical vibrational spectra in the fingerprint region were analysed for the comparison with an inelastic neutron scattering (INS) spectra, towards synergy between experiment and theory. INS spectroscopy has access to the region below 1000 cm-1 and is sensitive to hydrogen bond motions, enabling the characterisation of low energy vibrational modes of theaflavin conformers pre-radical capture. The antioxidant activity of theaflavin is associated with the stability of the antioxidant formed, post radical capture, as to prevent further damage to biological systems. The nature of this pronounced stabilisation at the atomic scale is unknown. To aid in its characterisation, a comprehensive conformational study of the antioxidant radical tea theaflavin by high-level computation DFT was performed. Conformational analysis of the antioxidant radical structures of theaflavin were generated by the radical scavenging mechanisms: hydrogen atom abstraction and hydrogen atom addition. The most stable antioxidant radical H-abstraction was either at the 2-H site in the C ring or the b-OH hydroxyl site in the B ring, in gas and in a solvent. H-addition to the e-C and c-C sites in the B’ ring yielded the most energetically stable antioxidant radical.